Treatment of 5 dogs with immune-mediated thrombocytopenia using Romiplostim. Issue 1 (December 2016) - Kohn, Barbara; Bal, Gürkan; Chirek, Aleksandra; Rehbein, Sina; Salama, Abdulgabar
Abstract Background Immune thrombocytopenia (ITP) in dogs is analogous to that in humans. Romiplostim, a novel thrombopoietin receptor (TPO-R) agonist, is currently used for the treatment of refractory ITP in humans, but not in dogs. Here, we describe the response to romiplostim in five dogs with refractory ITP. Five dogs with severe and refractory ITP (three primary and two secondary) received romiplostim subcutaneously. Four dogs were administered 3–5 μg/kg and one dog received 10–13 μg/kg body weight once weekly. Results Romiplostim was well-tolerated and administration was associated with an increase in platelet counts in all five dogs. Four of the five dogs entered remission and relapses were not observed over a follow-up period of 3–10 months. Conclusions Romiplostim is effective in the treatment of ITP in dogs at least as well as in humans. This finding may help to develop and use new therapeutics for ITP in dogs and humans.